Professional competencies of architecture graduates: perceptions from graduates, academics and employers in the Nigerian construction industry / Joy Joshua Maina. - Maina, Joy Joshua (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2018)
The clamour for better quality graduates by architects in the Nigerian Construction Industry (NCI) necessitates a look into the core competencies and the adequacy of architecture education in preparing architecture graduates for professional practice. 116 self-report likertscale questionnaires from architecture graduates (2009-2015), academics and employers were analysed to establish core competencies developed by the graduates while in school. Descriptive statistics, t-tests as well as Mann-Whitney tests for differences in ratings were employed for the study. Results reveal the perceived adequacy of architecture education for the future career of graduates from the academic perspective. Graduates were most proficient at design related competencies while AutoCAD was still considered the most important CAD competency for architecture graduates in the NCI. The study recommends more frequent evaluations of competencies for employability in collaboration with industry as well as embracing BIM related software in line with global best practices.